Language and the Sensing Body: How Sensoriality Permeates Syntax in Interaction - Mondada, Lorenza (Frontiers in Communication, 2021)
The paper explores the grammar-body interface by examining the intertwinement of embodied practices and turns at talk, where the sensing body permeates the ongoing syntax, in particular in activities in which the participants are engaged in talking about sensorial features while at the same time experiencing them, for instance in tasting sessions. So, the question tackled concerns how situated feelings, sensory experiences, and perceptive actions are embedded in the ongoing talk, and how they shape its emergent syntax, possibly affecting its smooth progressivity. The study shows how the choice of specific syntactic formats can be systematically related to the complex ecology of embodied actions, namely to publicly accountable ways of sensing material objects, to ways of showing and addressing an audience, and to visible ways of referring to standard documents normatively defining tasting descriptors. The syntactic formats described and their specific temporal realizations are thus deeply rooted in the local material ecology, in which they not only reproduce a normative model but reflexively express the senses with words and sensuously feel the words.